Investigation on the adhesion improvement of organic coatings on the surface of hot-dip galvanized steel. (August 2020) - Zhu, L Z; Liang, Y J; Yang, J H; Chen, X
Abstract: In order to solve the problem of poor adhesion of organic coatings on the surface of hot-dip galvanizing, we conducted a series of experiments to select the suitable pre-treatment method and type of the coatings. We adopted temperature shock & alternating damp heat combined test and waterproof test to simulate the service conditions, and investigated the adhesion of organic coating on the surface of hot-dip galvanizing in the wet environment. With the XPS analysis, we discussed the avoidance of formation of weak boundary layer on the hot-dip galvanizing surface by pre-treatment, and the improvement on adhesion of the organic coatings. We also proposed the pre-treatment method of coupling treatment with silane or combined alkali washing & grinding procedures, by which the organic coating on the hot-dip galvanizing surface performed excellent adhesion and water proof ability against wet conditions.